Sun Kings cross the outback [solar powered vehicles marathon]. - Zorpette, G. (IEEE spectrum)
The University of Michigan's solar racing team showed its mettle in the gruelling World Solar Challenge marathon. To win the race required state-of-the-art solar cells, batteries, electronics and the integration of mechanical, aerodynamics, and materials science